THE NORMATIVE ROLE OF FAMILY BUSINESS ETHICS IN SHAPING THE INTEGRATION OF FINANCIAL REPORTING AT THE HERLY SHOP MSME IN AMBON CITY - Tasya Salamin; Wa Inje Tomia; Hamida; Umaira W.S Rumanama; Rindi Rahareng (PT. Jurnal Center Indonesia Publisher, 2026)
Family-owned MSMEs (MSMEs) play a vital role in the local economy, but they still face challenges in financial management and reporting, particularly regarding the mixing of personal and business finances. This community service project aims to implement the normative role of family business ethics in integrating financial reporting at the Herly MSME Store in Ambon City. The method used was Participatory Action Research through interviews, group discussions, training, and mentoring. The activity focused on internalizing family business ethics values and implementing a simplified financial reporting system based on the Indonesian MSME Financial Accounting Standards (SAK). The results demonstrated increased understanding, skills, and changes in attitudes toward financial transparency and accountability. The integration of family business ethics has been shown to support more structured and sustainable financial reporting.